Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Suppose that $f$ is analytic in a simply connected domain $D$ containing distinct points $z_1, z_2 ,\ldots,z_n $ and that $\gamma$ is simple closed curve enclosing $z_1, z_2 ,\ldots,z_n $.

Set $w(z)= \prod _k_{=1}^n (z-z_k)$ . Prove that

$$P(z) =\int_{\gamma} \frac {f(\zeta)}{w(\zeta)} \frac{w(\zeta)-w(z)}{\zeta-z}d\zeta$$ defines a polynomial of degree $n-1$ satisfying $P(z_k) =f(z_k), k =1,2,3,\ldots,n.$

I don't know what thought I am suppose to present here. What I just know is to do the partial fraction of the $w(z)$. Then I just stuck not knowing the fact I am using here. This is actually a recent comprehensive exam question which I could not solve. My professor gave me some hint but that also did not help. The idea of partial fraction came out of his mouth. But I don't remember what he told me to do to complete the problem. I really wish to see the detail solution of the problem. Thanks in advance.


Partial Fraction of $\frac{1}{w(\zeta)}= \frac {1}{\prod _k_{=1}^n (\zeta-z_k)}$ is given by $$\frac {A_1}{\zeta-z_1}+\frac {A_2}{\zeta-z_2}+\cdots+\frac {A_n}{\zeta-z_n}$$

Where each $A_i = \frac{1} {\prod_j_{=1}^n z_i-z_j} , j \neq i$

Sorry I missed that not equal to part, I don't know how to accomodate that in the product, any edit appreciated.

share|cite|improve this question
You could add the partial fraction as an additional information since you already calculated it. – saz Dec 31 '12 at 16:53
up vote 2 down vote accepted

Let $$P_j(z) := \prod_{k=1}^j (z-z_j)$$ (Then $w(z)=P_n(z)$ by definition.) As you already mentioned it's a good idea to do partial fraction. We have

$$\begin{align}w(\xi)-w(z) &= ((\xi-z)+(z-z_n)) \cdot P_{n-1}(\xi) - (z-z_n) \cdot P_{n-1}(z) \\ &= (\xi-z) \cdot P_{n-1}(\xi) + (z-z_n) \cdot (P_{n-1}(\xi)-P_{n-1}(z)) \tag{1}\end{align}$$


$$\frac{w(\xi)-w(z)}{\xi-z} = P_{n-1}(\xi) + \frac{z-z_n}{\xi-z} \cdot (P_{n-1}(\xi)-P_{n-1}(z)) \tag{2}$$

Now we do the same step as in (1) again and obtain

$$\begin{align}P_{n-1}(\xi)-P_{n-1}(z) &= (\xi-z) \cdot P_{n-2}(\xi) + (z-z_{n-1}) \cdot (P_{n-2}(\xi)-P_{n-2}(z)) \\ \stackrel{(2)}{\Rightarrow} \frac{w(\xi)-w(z)}{\xi-z} &= P_{n-1}(\xi) + \underbrace{(z-z_n)}_{=:Q_1(z)} \cdot P_{n-2}(\xi) + \frac{(z-z_n) \cdot (z-z_{n-1})}{\xi-z} \cdot (P_{n-2}(\xi)-P_{n-2}(z)) \end{align}$$

By induction we obtain

$$\frac{w(\xi)-w(z)}{\xi-z}= \sum_{j=1}^m Q_{j-1}(z) \cdot P_{n-j}(\xi) + \frac{Q_m(z)}{\xi-z} \cdot (P_{n-m}(\xi)-P_{n-m}(z))$$

where $Q_j(z) := \prod_{k=n-j}^n (z-z_j)$, $Q_0(z):=1$. This works fine for $m \leq n-2$. In the last step (where the remaining polynomial has degree 1), i.e. $m=n-1$, we obtain

$$\begin{align} \frac{w(\xi)-w(z)}{\xi-z}&= \sum_{j=1}^{n-1} Q_{j-1}(z) \cdot P_{n-j}(\xi) + \frac{Q_{n-1}(z)}{\xi-z} \cdot ((\xi-z_1)-(z-z_1)) \\ &= \sum_{j=1}^{n-1} Q_{j-1}(z) \cdot P_{n-j}(\xi) +Q_{n-1}(z) \tag{3} \end{align}$$

Now we are done: By using (3) in the definition of $P$ we obtain

$$\begin{align} P(z) &= \int_{\gamma} \frac{f(\xi)}{w(\xi)} \cdot \left( \sum_{j=1}^{n-1} Q_{j-1}(z) \cdot P_{n-j}(\xi) +Q_{n-1}(z) \right) \, d\xi \\ &= \sum_{j=1}^{n-1} Q_{j-1}(z) \cdot \underbrace{\int \frac{f(\xi)}{w(\xi)} \cdot P_{n-j}(\xi) \, d\xi}_{=:a_j} + Q_{n-1}(z) \cdot \underbrace{\int_{\gamma} \frac{f(\xi)}{w(\xi)} \, d\xi}_{=:b} \end{align}$$

Note that $Q_j$ are polynomials of degree $\leq n-1$ (and that the constants $a_j$, $b$ do not dependent on $z$). This shows that $P$ is polynomial of degree n-1.

Last but not least: $$P(z_k) = \int_{\gamma} \frac{f(\xi)}{w(\xi)} \cdot \frac{w(\xi)-0}{\xi-z_k} \, d\xi = \int_{\gamma}\frac{f(\xi)}{\xi-z_k} \, d\xi = 2\pi \imath \cdot f(z_k)$$ where we applied Cauchy's integral formula (and used $w(z_k)=0$). (So if you would like to have $P(z_k) = f(z_k)$ you should add the factor $\frac{1}{2\pi \imath} \cdots$ in your definiton of $P$.)

share|cite|improve this answer
is something wrong on $(1)$. I could not see that one. – Deepak Dec 31 '12 at 18:46
@Deepak There was a typo, should be fine now. – saz Dec 31 '12 at 19:48

First note that $$ \frac{w(\zeta) - w(z)}{\zeta - z} $$ is in fact a polynomial in $(\zeta, w)$ and therefore does not have any poles as a function of $\zeta$ . The only poles come from $w(\zeta)$ in the denominator and they are located at $z_1, \dotsc, z_n$. If $z \not \in \{z_1, \dotsc, z_n \}$ an easy calculation shows that the residue at $z_k$ equals $$ \frac{f(z_k)}{w'(z_k)} \frac{w(z)}{z-z_k}.$$ This gives the relation

$$ P(z) = 2 \pi i \sum_{k=1}^n \frac{f(z_k)}{w'(z_k)} \frac{w(z)}{z-z_k} $$

which is a polynomial of degree at most $n-1$ and therefore this equality extends to all $z$. Use $$ \lim_{z \to z_k} \frac{w(z)}{z-z_k} = w'(z_k) $$ to quickly verify that $P(z_k) = 2 \pi i \, f(z_k)$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.